2023
DOI: 10.1002/pul2.12298
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying 4D flow cardiovascular magnetic resonance vortices in patients with pulmonary hypertension: A pilot study

Ali Borhani,
Kristin K. Porter,
Muhammad Umair
et al.

Abstract: In this 4D flow cardiovascular magnetic resonance (CMR) study, vortical blood flow in the main pulmonary artery (MPA) is quantified using circulation (ᴦ), a metric used in fluid dynamics to quantify the rotational components of flow. Circulation (ᴦ) is a 4D flow CMR metric that quantifies the vortical blood flow pattern in the MPA of patients with pulmonary hypertension (PH), distinguishes them from healthy controls, and shows high correlation with invasive markers of PH severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In patients with various type of pulmonary hypertension, RHC-measured mPAP has shown better correlation with the persistency of 4D flow-derived vortices in the pulmonary artery across the cardiac cycle rather than echocardiography-derived mPAP. 42,43 PAWP was proven to be correlated with left atrial peak inflow acceleration. 44 Despite the potential usefulness of these techniques further studies are needed in the specific context of advanced HF.…”
Section: Flows 4d Flow and Haemodynamicmentioning
confidence: 98%
See 1 more Smart Citation
“…In patients with various type of pulmonary hypertension, RHC-measured mPAP has shown better correlation with the persistency of 4D flow-derived vortices in the pulmonary artery across the cardiac cycle rather than echocardiography-derived mPAP. 42,43 PAWP was proven to be correlated with left atrial peak inflow acceleration. 44 Despite the potential usefulness of these techniques further studies are needed in the specific context of advanced HF.…”
Section: Flows 4d Flow and Haemodynamicmentioning
confidence: 98%
“…Moreover, different studies confirmed how 4D flow CMR is useful for estimating right catheterization (RHC) derived parameters such as mean pulmonary arterial pressure (mPAP) or pulmonary artery wedge pressure (PAWP). In patients with various type of pulmonary hypertension, RHC‐measured mPAP has shown better correlation with the persistency of 4D flow‐derived vortices in the pulmonary artery across the cardiac cycle rather than echocardiography‐derived mPAP 42,43 . PAWP was proven to be correlated with left atrial peak inflow acceleration 44 …”
Section: Flows 4d Flow and Haemodynamicmentioning
confidence: 99%